Analysis of factors associated with adolescent sexual behavior - Fitriani; Amir, Eka; Samosir, Marlina (Journal of Midwifery and Nursing, 2024)
Adolescence is a time full of turmoil and during this period teenagers have great curiosity and begin to seek freedom. Adolescence is a period that is vulnerable to negative influences, such as free sex, drugs, crime and rape which can endanger them because they can contract venereal diseases, especially AIDS. Premarital sexual behavior in teenagers is a problem that often occurs and many teenagers have had sex. There are several factors related to premarital sexual behavior, such as mental health, knowledge, peers and information media. The aim of this research is to analyze factors related to premarital sexual behavior in adolescents. This research method uses analytical survey research, namely a survey or research that tries to explore how and why the phenomenon of adolescent sexual behavior occurs. Data was obtained through interviews using a questionnaire measuring tool. Data analysis was carried out using univariate and bivariate methods and testsChi-square. The results of this study indicate that respondents are at risk of engaging in premarital sexual behavior on mental healthP-value = 0.001, knowledgeP-value = 0.000, peersP-value = 0.000, and information mediaP-value = 0.001 so that the bivariate results obtained: Mental health, knowledge, peers and information media are related to free sexual behavior in adolescents. Based on the results of this research, it is hoped that there will be programs that can increase knowledge, such as counseling, dissemination of correct sexual information and parental supervision of adolescent children